Catalytic performance of Fe3O4 nanoparticles for cyclocondensation synthesis of thiacrown ethers. (30th December 2014) - Lin, Shangxin; Chen, Yajie; Tan, Xiepeng; Song, Feng; Yue-Bun Pun, Edwin; He, Zhubing; Pu, Jixiong
Abstract: The catalytic function of nanoparticles is one the most successful applications of nanotechnologies so far. A novel and mild one-pot cyclocondensation reaction catalyzed by Fe3 O4 nanoparticles is achieved for the first time in this work. By the function of those nanoparticles, the thiacrown ethers, including both 1, 4-dithiane and 1, 4, 7-trithiacyclononane were obtained with considerable yield and turnover in a milder condition than that of the conventional routes. The excellent dehydrating ability and acid sensitivity of Fe3 O4 nanoparticles were discovered in a series of experiments of esterification of DL-malic acid. The catalytic reaction mechanism of Fe3 O4 nanoparticles was explored through the investigation of morphology evolution of those nanoparticles by transmission electron microscopy. Interestingly, the as-prepared big nanoparticles were decomposed into hollow or loose bounded aggregates of smaller nanoparticles after catalytic cycles. The result shown in this work claims promising utilization of Fe3 O4 nanoparticles with big potential in catalytic synthesis.